Investigation of Thermoelectric Properties of a Two-Dimensional Janus Si2SbBi and non-Janus SiSb using Computational Method Density-Functional Theory - Yusuf Affandi; Muhammad Yusrul Hanna (Jurnal Elektronika dan Telekomunikasi, 2023)
Two-dimensional materials are of considerable interest owing to their unique electronic and thermal properties. In this study, we investigate the thermoelectric (TE) potential of two-dimensional Janus Si2SbBi and compare it with that non-Janus SiSb based on the density-functional theory (DFT) calculations. According to the DFT calculations, both materials exhibit semiconductor properties with bandgaps of 0.728 eV (Janus Si2SbBi) and 0.82 eV (SiSb), respectively. Having information on the energy band structure, we evaluated TE properties using the Boltzmann transport equations as a function of Fermi energy as implemented in BoltzTraP2 code. We find a Seebeck coefficient of 1349 (1342)  for -type ( -type) dopingat T = 300 K of the Si2SbBi monolayer. The results of our study present that the Janus Si2SbBi monolayer possesses a high Seebeck coefficient and electrical conductivity, leading to a substantial power factor (PF) of    at 300 K. The PF increase with increase in temperature and has the highest peak value up to  at 600 K. The results show that the Seebecek coefficient, electrical conductivity and power factor of the Janus Si2SbBi monolayer are greater compared to those of non-Janus SiSb monolayer. Our study presents Janus Si2SbBi as a potential thermoelectric candidate, highlighting its prospective use in advanced thermoelectric applications.